Are We ‘Smarter’ Now? Case Study of Smart School Implementation in a Developing Nation - Zaenab, S. Majeed; Zailin Shah, Yusoff (Macrothink Institute, 2015)
This study was aimed at investigating ICT adoption at a Smart School in Malaysia. A questionnaire gathering data on the tools and applications used by teachers as well factors affecting teachers’ adoption of ICT in teaching was administered to 73 teachers and one administrator while 10 teachers and the administrator were interviewed to gain a deeper understanding of the reasons for the responses given in the questionnaire. Frequencies and percentages were calculated while emerging themes from the interviews were recorded for analysis. The results revealed that the participants were at the Utilisation level of ICT adoption even though most of them have positive attitudes toward ICT adoption which means that they were willing to use ICT, specifically computers, in the classroom. The participants used ICT tools to prepare exam materials, content, worksheets and handouts for their teaching. However, the factors that influenced participants’ ICT adoption were: one, using ICT in teaching took up too much time, two, the school management did not provide enough ICT facilities and training to improve ICT skills was needed and three, even though the school management supported ICT adoption they did not put it as a priority. In conclusion, the findings indicated that the participants were positive about the adoption but several factors are barriers which could have affected their progress from lower level to a higher level adoption. Recommendations include allocation of time to prepare ICT resources and lesson, further training for teachers and increase in the number of computers at the school.